Can Quizizz Support Legal English Learning? Evidence from Law Students and Lecturers - Thanh-Huong Nhac; Nguyet-Huong Nguyen Dang (VELES Voices of English Language Education Society, 2026)
Technology-enhanced learning tools are increasingly used to support interactive and student-centered instruction in higher education, yet their role in discipline-specific English courses remains insufficiently examined. This mixed-methods descriptive study investigated law students’ and Legal English lecturers’ perceptions of Quizizz as a supplementary tool for Legal English instruction. The study involved 178 law students from Cohorts 46 and 47 who completed a 16-item five-point Likert-scale questionnaire and three Legal English lecturers who participated in semi-structured interviews. Quantitative data were analyzed using SPSS 26.0 to calculate item means and standard deviations. In contrast, qualitative interview data were analyzed thematically to explain lecturers’ experiences of using Quizizz in Legal English lessons. The findings showed that students generally perceived Quizizz positively, especially for reviewing Legal English vocabulary and terminology, supporting flexible practice, providing immediate feedback, and increasing motivation. The highest-rated item was the effectiveness of Quizizz for learning and reviewing Legal English vocabulary and terminology, indicating that students viewed the platform as particularly useful for repeated exposure to specialized legal language. Lecturers also considered Quizizz practical for reinforcing lesson content, conducting formative assessment, monitoring students’ progress, and making terminology review more engaging. However, both students and lecturers identified several limitations, including unstable internet connection, limited device access, the time required to design suitable quizzes, and Quizizz’s restricted capacity to assess complex Legal English skills such as speaking, writing, legal reasoning, and argument construction. These findings suggest that Quizizz can support Legal English instruction when used as a supplementary tool for vocabulary review, grammar practice, formative assessment, and self-paced learning. However, it should be combined with the lecturer's explanation, legal case discussions, and productive language tasks to promote deeper ESP learning.